2008
DOI: 10.2106/jbjs.g.00421
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-up of Radial Shortening Osteotomy for Kienböck Disease

Abstract: Although most patients had mild wrist pain, patient satisfaction and the clinical results were satisfactory following a radial shortening osteotomy. This procedure is a reliable long-term treatment for Lichtman stage-II and IIIA disease and may be a reasonable option for patients with stage-IIIB disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 13 publications
4
56
0
14
Order By: Relevance
“…[2][3][4][5][6][7][8] In addition, revascularization of the diseased lunate was achieved by this osteotomy. 7 Several biomechanical studies have demonstrated that radial shortening can unload the lunate by shifting the load toward the distal ulna.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8] In addition, revascularization of the diseased lunate was achieved by this osteotomy. 7 Several biomechanical studies have demonstrated that radial shortening can unload the lunate by shifting the load toward the distal ulna.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported a satisfactory clinical outcome after this procedure for Kienböck disease. [2][3][4][5][6][7][8] In addition, previous experimental and theoretical studies have supported this osteotomy as being an effective extraarticular procedure to reduce the load on the diseased lunate. 9 -13 Although these biomechanical studies have clarified unloading the lunate after radial shortening, the obtained results may be achieved under nonphysiological loading conditions.…”
mentioning
confidence: 90%
“…Since then, different types of vascularized bone graft have been suggested to treat Kienböck disease. 11,12 Because some studies [13][14][15] have reported many complications related to joint-leveling procedures, including nonunion, infection, and ulnar impingement, and the need for plate removal in most patients undergoing radial shortening, the authors of this study performed lunate core decompression. The purpose of this study was to report the medium-term results of lunate core decompression for Kienböck disease.…”
mentioning
confidence: 99%
“…Some authors do not recommend radial shortening at advanced stages of lunatomalacia. [12] this is due to the fact that osteotomy at this stage does not correct position of scaphoid [34,35,36]. In their study Croog et al [6,28] stated that proximal row carpectomy was a reliable surgical method for Lichtman Stage IIIA and IIIB disease.…”
Section: Discussionmentioning
confidence: 99%